Income distribution and the Great Depression - Christian A. Belabed (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2015)
There is a growing literature comparing the current financial crisis or Great Recession to the worst economic crisis of capitalism, the Great Depression. However, the role of rising income inequality, which has risen dramatically before both crises, is rarely discussed. In this paper we discuss the rise of top-end inequality and its effects on household consumption, saving, and debt for the 1920s by applying a non-standard theory of consumption, the relative income hypothesis, to the period of interest. We argue that income inequality is linked to the increase of household consumption and the simultaneous decline of household savings as well as rapidly increasing household debt. Thus, the rise of top-end inequality in connection with a broader institutional change, such as the deregulation of financial markets, has contributed to a build-up of financial and macroeconomic instability, in the period leading to the Great Depression. – – Ein wachsender Teil der akademischen Literatur vergleicht die aktuelle Finanz- und Wirtschaftskrise mit der größten wirtschaftlichen Krise des Kapitalismus, der Großen Depression. Dennoch wird in der Literatur die Rolle der Einkommensungleichheit, die vor beiden Krisen stark gestiegen ist, selten diskutiert. In diesem Papier werden die Effekte einer steigenden Ungleichverteilung der Einkommen auf Konsum, Ersparnis und Verschuldung diskutiert. Dabei greift dieses Papier auf eine Nicht-Standard Theorie des Haushaltskonsums, die Relative Einkommenshypothese, zurück. Es wird argumentiert, dass steigende Einkommensungleichheit sowohl mit dem Anstieg des privaten Konsums und dem gleichzeitigen Rückgang der Sparquote als auch mit dem Anstieg der privaten Haushaltsverschuldung ursächlich verbunden ist. Somit hat der Anstieg der Einkommensungleichheit, in Verbindung mit einem bis dahin beispiellosen institutionellen Wandel auf den Finanzmärkten, zum Aufbau finanzieller und makroökonomischer Instabilität in den 1920-er Jahren geführt.
Keywords: D31; D33; E21; E25; N12; N22; N32; N62; 330; income distribution; relative income hypothesis; household debt; financial innovation; great depression